Perencanaan Aplikasi E-Commerce “Lokanara” Berbasis Web dengan Terverifikasi Produk berbasis QR - Rangga Galih Wardani; Arya Kusumadewa; Rafi Nabil Bahtiar; Alya Nur Samiya (Lembaga Pengembangan Kinerja Dosen, 2025)
Advances in digital technology encourage Micro, Small, and Medium Enterprises (MSMEs) to integrate digital platforms in order to expand the reach of product marketing. This digital transformation provides a great opportunity for MSMEs to reach a wider range of consumers, both in the national and international markets. By utilizing technology, MSMEs can increase marketing effectiveness, speed up transactions, and strengthen brand image. However, the main challenge faced is the low level of consumer confidence in the authenticity, quality, and legality of local products. The number of counterfeit products in the online market and the lack of verified information are serious obstacles that can reduce the competitiveness of MSMEs in the midst of global competition. This research aims to design and develop an e-commerce platform called